Determination of the chemical composition of the essential oil from Arazá (Eugenia stipitata) leaf residues and possible agroindustrial applications: Agroindustry - Tasambay Salazar, Angélica María (2025)
The use of plant waste is a topic of current interest due to the environmental effects it causes on the environment. The waste from the leaves of Arazá (Eugenia stipitata Mc Vaugh) is not used in Ecuador and in the Amazonian Experimental Research and Production Center, located in the canton of Santa Clara, province of Pastaza, a significant amount of waste is obtained from this type of crop. , therefore the objective of the study was to determine the chemical composition of its essential oil, using three extraction methods, to evaluate the effectiveness of these methods in terms of performance and establish their possible applications in the agroindustrial area. Three methods were used to extract the essential oil: steam drag, maceration and ultrasound-assisted extraction; To determine the chemical components, gas chromatography coupled to mass  spectrometry was used. The results determined that ultrasound-assisted extraction turned out to be more efficient, with a yield of 2.17%, Phenols (47.75%), Hydrocarbons (35.51%), Acids and Esters (6.10%) were identified as major components; In steam distillation, although less efficient in terms of 0.01% yield, Terpenes (57.57%), Alcohols and Other Compounds (36.57%), Sesquiterpenes (5.85%) were identified; and in the case of maceration it gave a 1.5% yield, Phenols (75.84%), Esters and Acids (12.91%) and Amides (6.17%) were identified. This rich composition of bioactive components highlights its importance as waste due to its applications in the food, pharmaceutical, cosmetic and phytosanitary industries.